Age-related macular degeneration: suitability of optogenetic therapy for geographic atrophy - Borchert, Grace A.; Shamsnajafabadi, Hoda; Ng, Benjamin W. J.; Xue, Kanmin; De Silva, Samantha R.; Downes, Susan M.; MacLaren, Robert E.; Cehajic-Kapetanovic, Jasmina (Frontiers in Neuroscience, 2024)
Age-related macular degeneration (AMD) is a growing public health concern given the ageing population and it is the leading cause of blindness in developed countries, affecting individuals over the age of 55 years. AMD affects the retinal pigment epithelium (RPE) and Bruch's membrane in the macula, leading to secondary photoreceptor degeneration and eventual loss of central vision. Late AMD is divided into two forms: neovascular AMD and geographic atrophy (GA). GA accounts for around 60% of late AMD and has been the most challenging subtype to treat. Recent advances include approval of new intravitreally administered therapeutics, pegcetacoplan (Syfovre) and avacincaptad pegol (Iveric Bio), which target complement factors C3 and C5, respectively, which slow down the rate of enlargement of the area of atrophy. However, there is currently no treatment to reverse the central vision loss associated with GA. Optogenetics may provide a strategy for rescuing visual function in GA by imparting light-sensitivity to the surviving inner retina (i.e. retinal ganglion cells or bipolar cells). It takes advantage of residual inner retinal architecture to transmit visual stimuli along the visual pathway, while a wide range of photosensitive proteins are available for consideration.Herein, we review the anatomical changes in GA, discuss the suitability of optogenetic therapeutic sensors in different target cells in pre-clinical models, and consider the advantages and disadvantages of different routes of administration of therapeutic vectors.